2021
DOI: 10.3390/antibiotics10060697
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Risk of Aortic Aneurysm/Aortic Dissection and the Use of Fluroquinolones: A Systematic Review and Meta-Analysis

Abstract: This study aimed to investigate the association between the risk of aortic aneurysm (AA)/aortic dissection (AD) and the use of fluoroquinolones (FQs). PubMed, Embase, Cochrane CENTRAL, Cochrane Database of Systematic Reviews, Web of Science and Scopus were searched for relevant articles to 21st February 2021. Studies that compared the risk of AA/AD in patients who did and did not receive FQs or other comparators were included. The pooled results of nine studies with 11 study cohorts showed that the use of FQs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…[28][29][30][31][32] Several systematic metaanalyses found that the risk of aortic aneurysm and aortic dissection is significantly higher among the users of FQs. [33][34][35][36][37][38] Moreover, a retrospective cohort study of Taiwan National Health Insurance Research Database determined that the risk of all-cause mortality, aortic death, and later aortic surgery was found to be higher among the patients with aortic aneurysm or aortic dissection, who are exposed to systemic FQs. 39 Similarly, another retrospective cohort study of Taiwan National Health Insurance Research Database revealed that the mortality was increased in patients who took FQs to treat UTIs compared to the users of cephalosporins, 40 and a nested case-control study of Korea National Health Insurance data stressed on higher incidence of aortic aneurysm or aortic dissection among the users of systemic FQs.…”
Section: Aortic Aneurysmmentioning
confidence: 99%
“…[28][29][30][31][32] Several systematic metaanalyses found that the risk of aortic aneurysm and aortic dissection is significantly higher among the users of FQs. [33][34][35][36][37][38] Moreover, a retrospective cohort study of Taiwan National Health Insurance Research Database determined that the risk of all-cause mortality, aortic death, and later aortic surgery was found to be higher among the patients with aortic aneurysm or aortic dissection, who are exposed to systemic FQs. 39 Similarly, another retrospective cohort study of Taiwan National Health Insurance Research Database revealed that the mortality was increased in patients who took FQs to treat UTIs compared to the users of cephalosporins, 40 and a nested case-control study of Korea National Health Insurance data stressed on higher incidence of aortic aneurysm or aortic dissection among the users of systemic FQs.…”
Section: Aortic Aneurysmmentioning
confidence: 99%
“…Neither of the studies referred to H. pylori eradication and no case presentation is known. Clinically, one can hardly believe that 7–14 days of FQ treatment could change the aortic architecture [ 52 ]. Instead, during the decades of infection, H. pylori itself could promote the development of vascular complications (coronary heart disease, stroke, etc.)…”
Section: New Antibioticsmentioning
confidence: 99%
“…31 A 2021 meta-analysis stated that the risk of AA/AD with fluoroquinolone use was similar to that with other broad-spectrum antibiotics. 32 The authors have affected the results, such as computed tomography, blood pressure, body mass index, tobacco use, congenital collagen disorders, ongoing infection, and family history of aortic disease. 31 Future studies should attempt to control for as many potential confounders as possible.…”
Section: Study Limitationsmentioning
confidence: 99%